Relationship of Social, Family Support and Self-Efficacy on Complications Prevention of Mellitus Diabetes - Osita Putri; Lilik Pranata; Vausta Nurjanah (Sorume Health Sciences Journal, 2020)
Diabetes mellitus (DM) is a chronic disease that usually occurs in adults. Prevention of complications of diabetes mellitus can be done with several management which includes nutritional management, educational exercise and pharmacological therapy. In addition, factors that can support the prevention of complications include social support, family support and self-efficacy. This study aims to determine the relationship of social support, family and efficacy on the prevention of complications in diabetes mellitus sufferers at Palembang Health Center. This research is a quantitative study with an analytic survey design using a cross sectional design. The number of samples in this study were 46 respondents using the Kendall Tau statistical test. The results of the analysis using the Kendall Tau test showed that there was no relationship between social support and the prevention of complications with a value of p = 0.735. Then also found that there was no relationship between family support and prevention of complications of diabetes mellitus with a value of p = 0.76. While the results of the correlation test for the relationship between the efficacy of the prevention of complications of diabetes mellitus were also obtained p value = 0.323. From the results that have been obtained, it is expected that people with diabetes mellitus can prevent complications properly. In preventing complications in diabetes mellitus, it is hoped that it can involve families and people in the surrounding environment, so as to prevent complications maximally